2020
DOI: 10.3389/fpsyg.2020.563558
|View full text |Cite
|
Sign up to set email alerts
|

Self-Identity and Career Success of Nurses in Infectious Disease Department: The Chain-Mediating Effects of Cognitive Emotion Regulation and Social Support

Abstract: There has been some research conducted regarding nurses’ career success aimed at exploring its influencing factors, but there is no research on the mechanism of self-identity on the career success of infection control nurses. In order to further explore the formation mechanism of career success of nurses, we conducted our study using the Kaleidoscope Career Model to explore the chain-mediating effects of cognitive emotion regulation and social support between self-identity and career success. Five hundred fort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 57 publications
2
8
0
Order By: Relevance
“…The Chinese male nurses' career success in our study is similar to previous studies which found the level of career success of nurses is low (Dan et al, 2018;Wu et al, 2020;L. G. Zhang & Jin, 2018), and among the male nurses' career success, the score of the career competence dimension is the lowest.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The Chinese male nurses' career success in our study is similar to previous studies which found the level of career success of nurses is low (Dan et al, 2018;Wu et al, 2020;L. G. Zhang & Jin, 2018), and among the male nurses' career success, the score of the career competence dimension is the lowest.…”
Section: Discussionsupporting
confidence: 88%
“…When it turns to nurses, it refers to positive psychological experience accumulated in nursing and sense of accomplishment related to hands‐on experience (Dan et al, 2018 ; Sönmez et al, 2021 ). A survey suggests that career success of nurses plays an important role in decreasing the turnover rate and improving quality of nursing service (Wu et al, 2020 ; Xu et al, 2021 ). Current research thus has a growing interest in exploring factors affecting male nurses' career development.…”
Section: Introductionmentioning
confidence: 99%
“…According to the articles search on CNKI and WOS, the research objects of career identity in the field of medicine and psychology are mainly medical students and nurses [35]. The research contents mainly include the status quo of medical students' career identity [36,37], nurses' career identity [24], career success [38], and job burnout [23]. For example, Liu et al's [39] research showed that the overall career identity of nurses was relatively low, and social support had a profound impact on the career identity of nurses.…”
Section: Main Research Hotspotsmentioning
confidence: 99%
“…Currently, studies on career success are mostly focused on the field of management, but in recent years, the number of studies on career fulfillment in the field of nursing field has gradually increased ( Wu et al, 2022 ). Previous studies have shown that career success has a significant positive predictive effect on nurses’ career identity and individual values, which is conducive to motivating nurses’ enthusiasm for work, improve the quality of nursing service, reduce the turnover rate of nurses and stabilize the nursing team ( Dan et al, 2018 ; Zamanzadeh et al, 2019 ; Wu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%